Modeling of Gas Transport through Polymer/MOF Interfaces: A Microsecond-Scale Concentration Gradient-Driven Molecular Dynamics Study - Ozcan, Aydin (Chem Mater, 2020)
[Image: see text] Membrane-based separation technologies offer a cost-effective alternative to many energy-intensive gas separation processes, such as distillation. Mixed matrix membranes (MMMs) composed of polymers and metal–organic frameworks (MOFs) have attracted a great deal of attention for being promising systems to manufacture durable and highly selective membranes with high gas fluxes and high selectivities. Therefore, understanding gas transport through these MMMs is of significant importance. There has been longstanding speculation that the gas diffusion behavior at the interface formed between the polymer matrix and MOF particles would strongly affect the global performance of the MMMs due to the potential presence of nonselective voids or other defects. To shed more light on this paradigm, we have performed microsecond long concentration gradient-driven molecular dynamics (CGD-MD) simulations that deliver an unprecedented microscopic picture of the transport of H(2) and CH(4) as single components and as a mixture in all regions of the PIM-1/ZIF-8 membrane, including the polymer/MOF interface. The fluxes of the permeating gases are computed and the impact of the polymer/MOF interface on the H(2)/CH(4) permselectivity of the composite membrane is clearly revealed. Specifically, we show that the poor compatibility between PIM-1 and ZIF-8, which manifests itself by the presence of nonselective void spaces at their interface, results in a decrease of the H(2)/CH(4) permselectivity for the corresponding composite membrane as compared to the performances simulated for PIM-1 and ZIF-8 individually. We demonstrate that CGD-MD simulations based on an accurate atomistic description of the polymer/MOF composite is a powerful tool for characterization and understanding of gas transport and separation mechanisms in MMMs.